Integration of Lean Management, Agile/Scrum, and PMBOK in Improving The UAT Process (A Case Study of Banking Co.) - Dedi Yusuf Hernanto; Gatot Yudoko (Riviera Publishing, 2026)
Digital transformation in the Indonesian banking industry has significantly in-creased pressure on software testing processes. At Banking Co., the number of features under testing rose by 295% between 2022 and 2024, from 5,840 to 43,595 features, while the existing UAT work procedures remained unchanged. This imbalance led to systematic waste, repeated rework, and increased burnout risk, threatening both operational sustainability and human capital. This study aims to identify dominant waste types in the UAT process, formulate an integrated Lean–Agile/Scrum–PMBOK solution, and analyze its potential impact on efficiency and team sustainability. A mixed methods approach was applied through a 65-item Likert survey targeting a population of 371 Testing Analysts, yielding 52 valid responses, and in-depth interviews with three expert informants from different management levels. Waste prioritization was analyzed using the Relative Im-portance Index (RII) and Composite RII. The findings identified seven categories of waste across 12 UAT activities, with Defects (0.756), Movement (0.735), and Waiting (0.725) ranking as the most dominant. The study also revealed a significant perception gap between practitioners and management regarding Movement waste, demonstrating the importance of triangulation in identifying hidden operational problems. Based on these findings, eight improvement op-tions integrating Lean Management, Agile/Scrum, and PMBOK principles were proposed, including Shared Accountability, System Stabilization, WIP Limit, Definition of Ready, and Lean-based UAT procedures. The results indicate that eliminating systemic waste could significantly reduce burnout risk and improve long-term team sustainability.